Evaluation of three methods for sampling ground-dwelling Ants in the Brazilian Cerrado - Lopes, Cauê T.(Univ. Federal de Uberlândia Instituto de Biologia); Vasconcelos, Heraldo L.(Univ. Federal de Uberlândia Instituto de Biologia) (Neotropical entomology, 2008)
Few studies have evaluated the efficiency of methods for sampling ants, especially in regions with highly variable vegetation physiognomies such as the Cerrado region of central Brazil. Here we compared three methods to collect ground-dwelling ants: pitfall traps, sardine baits, and the Winkler litter extractor. Our aim was to determine which method would be most appropriate to characterize the ant assemblages inhabiting different vegetation types. More species were collected with pitfall traps and with the Winkler extractor than with sardine baits. Pitfall traps collected more species in the cerrado (savanna) physiognomies, particularly in those with a poor litter cover, whereas the Winlker extractor was more efficient in the forest physiognomies, except the one subject to periodic inundations. There was a low similarity in species composition between forest and cerrado physiognomies, and this pattern was detected regardless of the method used to sampling ants. Therefore, even the use of a single, relatively selective method of collection can be enough for studies comparing highly distinct habitats and/or conditions. However, if the purpose of the sampling is to produce a more thoroughly inventory of the ant fauna, we suggest the use of a combination of methods, particularly pitfall traps and the Winkler extractor. Therefore, the Ants of the Leaf-Litter (ALL) Sampling Protocol appear to be an adequate protocol for sampling ants in the highly-threatened Brazilian cerrado biome. Poucos estudos avaliaram a eficiência de métodos para a coleta de formigas, especialmente em regiões com fisionomias vegetais bastante variáveis como a do Cerrado. Neste trabalho, foram comparados três métodos para a coleta de formigas do solo: armadilhas de solo, iscas de sardinha e o extrator de serapilheira de Winkler, com o objetivo de determinar o mais apropriado para caracterizar as assembléias de formigas associadas a diferentes tipos de vegetação. Mais espécies foram coletadas com armadilhas de solo e com o extrator de Winkler do que com iscas. As armadilhas de solo coletaram mais espécies nas fisionomias de cerrado (savânicas), particularmente naquelas com pobre cobertura de serapilheira, enquanto o extrator de Winkler foi mais eficiente nas fisionomias florestais, com exceção daquela sujeita a inundações periódicas. Houve baixa similaridade na composição de espécies entre as fisionomias de cerrado e florestais, e esse padrão foi observado com qualquer dos três métodos de coleta. Portanto, mesmo o uso de um único método pode ser suficiente em estudos que comparam condições ou hábitats bastante distintos. Entretanto, se o propósito da amostragem for produzir um inventário mais completo, sugerimos o uso de uma combinação de métodos, em particular as armadilhas de solo e o extrator de Winkler. Desse modo, o Protocolo para Amostragem de Formigas da Serapilheira (ALL Protocol) parece ser adequado para a amostragem de formigas na ameaçada região do Bioma Cerrado.